The Psychological Well-Being with Gender among Parents Who Have Autism Spectrum Disorder Children - Yosep, Iyus; Kirana, Anggita Dyah; Sismayadi, Zahrul Insan; Mardhiyah, Ai; Hikmat, Rohman (Poltekkes Kemenkes Semarang, 2024)
Background: Psychological well-being in a person is influenced by several factors, one of which is gender, where this factor is a differentiator between psychological well-being that is owned by a father or mother as a parent which will affect the ability to overcome problems that occur in the family, especially problems child health.Purpose: This study aims to determine differences in Psychological Well-Being viewed by gender in Depok City.Methods: The study population was parents who have children with autism spectrum disorder (ADS) at SEKOLAH LUAR BIASA Budi Lestari and Harapan Utama Ananda School. This type of research was quantitative with a correlation descriptive design. The sampling technique to be used was total sampling (n=30). Data collection was carried out on 23 â€“ 27 June 2022. The instrument in this research uses the Psychological Well-Being Scale (PWBS) instrument.Results: The results of data analysis obtained sig value. with a positive correlation coefficient of 0.695, which means that the strength of the relationship is strong.Discussion: The level of psychological well-being in each person is different. One of the factors that influence a person's psychological well-being is their belief in the roles they carry out on a daily basis. This gender difference determines how the parenting pattern is given or carried out by parents to their children.Conclusion: There is a strong and positive relationship between gender and parents with psychological well-being in parents who have children with autism spectrum disorder (ASD).Â